DUGAAN TINDAK PIDANA KORUPSI DALAM PENGADAAN TANAH UNTUK KEPENTINGAN UMUM - Aartje Tehupeiory (to-ra, 2015)
In terms of the provision of land for the public interest was formed the Committee for Land Procurement (P2T) based on the number of Presidential Decree No. 55 of 1993, with one of the principle is not looking for profit. Based on that, the Governor of Maluku made a decree on the city of Ambon in the decree for the construction of a common or garden Burial Tombs common (TPU). Because of thesituation/circumstances of the civil emergency in the province of Maluku, at the discretion of the Mayor of Ambon city as the Executive ruler of the elements of the civil emergency, delegated various tasks to the team's who had the responsibility to carry out the release of P2T land rights.But later in the day, a problem occurs that is alleged to have elements of criminal acts of corruption in the procurement of land for the public interest with respect to the construction of TPU. While all of the procedures and the mechanism of release of land rights has been carried out in accordance with Presidential Decree No. 55 no 1993. This is because the Government cannot took over the land purchase benefits.Therefore there needs to be re-construction (reconstruction) of losses the country associated with the procurement of land for the public interest. Kata kunci: Dugaan tindak pidana korupsi pengadaan tanah